"For a Socialist New Brunswick":: The New Brunswick Waffle, 1967-1972 - Webber, Patrick (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2009)
Abstract In 1970, several members of the New Brunswick New Democratic Party (NDP) formed a New Left/Trotskyist group within the party known as the New Brunswick Waffle. The NB Waffle gained significant strength within the NB NDP, eventually securing a victory for its radical manifesto, "For a Socialist New Brunswick," at a party convention in September 1971. A dispute, however, erupted over the legality of this victory, which led to a two-month split within the party that required intervention on the part of the federal NDP. By the end of 1971 the NB Waffle had itself fractured and collapsed.